LncRNA SNHG8 Promotes Proliferation and Inhibits Apoptosis of Diffuse Large B-Cell Lymphoma via Sponging miR-335-5p - Yu, Bing; Wang, Bo; Wu, Zhuman; Wu, Chengnian; Ling, Juan; Gao, Xiaoyan; Zeng, Huilan (Frontiers in Oncology, 2021)
Long-chain non-coding RNAs (LncRNAs) are expressed in DLBCL tissues and have been reported to play regulatory roles in diffuse large B-cell lymphoma (DLBCL), with cancer-promoting effect. This study aims to investigate the role of LncRNA SNHG8 in regulating DLBCL cells and uncover its underlying mechanism. The database of the Gene Expression Profiling Interactive Analysis (GEPIA) was searched and the expression of SNHG8 in DLBCL and normal tissues were examined. The expression of SNHG8 was evaluated in several DLBCL cell lines and a normal lymphocyte cell line. The short hairpin (sh)-RNA plasmids of SNHG8 were transfected into DLBCL cells to knock down the expression of SNHG8, and cell proliferation, colony formation, apoptosis, and expression of related proteins were assessed by corresponding experiments. The potential target of SNHG8 was predicted to be miR-335-5p by bioinformatics analysis. The interaction between SNHG8 and miR-335-5p was examined by dual luciferase assay. In addition, U2932 cells were co-transfected with or without sh-SNHG8 and miR-335-5p inhibitor, and then cell proliferation, colony formation and apoptosis were determined in the transfected cells. It was found that SNHG8 is overexpressed in various DLBCL tissues and cells, compared with normal counterparts. Knockdown of SNHG8 significantly inhibited cell proliferation and colony formation, while promote apoptosis of DLBCL cells. Furthermore, knockdown reduced the expression of Ki-67, proliferating cell nuclear antigen (PCNA) and Bcl-2, and enhanced that of Bax and cleaved-caspase 3/9. Additionally, miR-335-5p was down-regulated in DLBCL cell lines as compared with normal lymphocytes. Knockdown of SNHG8 increased miR-335-5p level, while miR-335-5p mimic decreased SNHG8 expression. The direct binding between SNHG8 and miR-335-5p was confirmed. Finally, the presence of miR-335-5p inhibitor partially canceled the inhibitory effects of SNHG8 knockdown on DLBCL cell proliferation and colony formation and the stimulating effects of SNHG8 knockdown on cell apoptosis. Taken together, our study suggested that lncRNA SNHG8 exerted a cancer-promoting effect on DLBCL via targeting miR-335-5p.